2014
DOI: 10.7498/aps.63.248107
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and structure of LuTaO4

Abstract: Since LuTaO4 is a scintillator host with the highest density, it is important to investigate the structure and phase transition for its single crystal preparation. The polycrystalline formed by the mixture of Lu2O3:Ta2O5 with the molar ratio 1:1 is prepared by solid state reaction method at different temperatures. The phase transitions and structures of the polycrystalline powders are investigated by X-ray diffraction and Rietveld refinement. The results show that the polycrystalline has a single phase M'-LuTa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The phase transition of the polycrystalline Lu 2 O 3 -Ta 2 O 5 with a molar ratio of 1 : 1 at high temperature has been studied by x-ray diffraction and Rietveld refinement, [18] which showed that the single phase M-LuTaO 4 or M -LuTaO 4 cannot be obtained from the melt of Lu 2 O 3 -Ta 2 O 5 with the molar ratio of 1 : 1. On the other hand, growing single crystal LuTaO 4 from the melt of Lu 2 O 3 and Ta 2 O 5 near the molar ratio 1 : 1 has been tried many times but is still unsuccessful, which indicates that it is necessary to obtain the detailed phase transition of Lu 2 O 3 -Ta 2 O 5 for the single crystal growth of LuTaO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The phase transition of the polycrystalline Lu 2 O 3 -Ta 2 O 5 with a molar ratio of 1 : 1 at high temperature has been studied by x-ray diffraction and Rietveld refinement, [18] which showed that the single phase M-LuTaO 4 or M -LuTaO 4 cannot be obtained from the melt of Lu 2 O 3 -Ta 2 O 5 with the molar ratio of 1 : 1. On the other hand, growing single crystal LuTaO 4 from the melt of Lu 2 O 3 and Ta 2 O 5 near the molar ratio 1 : 1 has been tried many times but is still unsuccessful, which indicates that it is necessary to obtain the detailed phase transition of Lu 2 O 3 -Ta 2 O 5 for the single crystal growth of LuTaO 4 .…”
Section: Introductionmentioning
confidence: 99%